Artificial Vision in 3D perspective. For object detection on planes, using points clouds - Catalina Alejandra Vázquez Rodriguez (International Journal of Combinatorial Optimization Problems and Informatics, 2013)
In this paper, we talk about an algorithm of artificial vision for the robot Golem - II + with which to analyze the environment the robot, for the detection of planes and objects in the scene through point clouds, which were captured with kinect device, possible objects and quantity, distance and other characteristics. Subsequently the "clusters" are grouped to identify whether they are located on the same surface, in order to calculate the distance and the slope of the planes relative to the robot, and finally each object separately analyzed to see if it is possible to take them, if they are empty surfaces, may leave objects on them, long as feasible considering a distance, ignoring false positives as the walls and floor, which for these purposes are not of interest since it is not possible to place objects on the walls and floor are out of range of the robot's arms.